Horticulture provides for nutrition, healthcare and fights off hunger - Malhotra, S K (Indian Farming, 2015)
Horticulture which was a pleasantry before independance, hasemerged as core sector in agriculture passing through the various phases. It is estimated that all the horticulture crops put together cover nearly 20.6 million ha area with an annual production of 214.7 million tonnes (2008-09). Though these crops occupy hardly 7% of the cropped area they contribute over 18% to the gross agricultural output in the country. Cultivation of these crops is labour intensive and as such they generate lot of employment opportunities for the rural population.